STUDI KELAYAKAN USAHA TERNAK AYAM BROILER DI DESA BADAL KECAMATAN NGADILUWIH KABUPATEN KEDIRI - Erlin Widya Fatmawati (Universitas Islam Balitar, 2022)
This research have two purpose was to determine the characteristics of breeders and to analyze the feasibility of broiler farming in Badal Village, Ngadiluwih District, Kediri Regency. The method used in this research is a survey method by conducting direct interviews with farmers. The method of analysis is carried out by calculating costs, income, BEP, R/C ratio, and MOS (Margin Of Savety). This livestock business occupies a location with a land area of ​​​​approximately 1000 m² which consists of a permanent cage building with a brick construction with a population of 20,000 chickens with a close house system. The results showed that this broiler breeder has a profit of Rp. 77.665.834,-/ production period. Based on the calculation of the BEP of the production unit, the results obtained are 37,564 kg per period production and rupiah BEP of Rp. 18,690, - per head. Calculation of the R/C ratio of 1.1 is said to be feasible. The results of the study can be concluded that the broiler farming business is feasible to continue to work on